Penyuluhan Kesehatan Gigi dan Mulut: Efektivitas Media Booklet, Flipchart, dan Video Animasi dalam Meningkatkan Pengetahuan - Nur Aida, Wanda; Liasari, Ira; Mirawati Hamid, Ellis (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental and oral health problems in Indonesia have increased based on the results of riskesdas in 2007 by 43.4% to 53.3% in 2013 and by 57.6% in 2018. The prevalence of caries in South Sulawesi is 55.54%, in the city Makassar as much as 52.09%, and in the 5-9 year age group as much as 65.51%. The source of dental health problems is generally closely related to oral hygiene maintenance behavior. To change bad behavior, one way is to intervene through education. The aim of this research is to determine the effectiveness of dental and oral health education using booklets, flipcharts, and animated videos to increase children's dental and oral health knowledge. This type of research has a pre-post test research design by providing three different intervention groups. Data analysis used the Friedman-Paired Test because the data was normally distributed. The research results showed that the p value m for the booklet and animated video media intervention group was 0.000 (p<0.05), which means that the booklet and animated video media were effective in increasing dental and oral health knowledge, while the p value for the flipchart intervention group was 0.115 (p>0.05), ) means that flipchart media is not effective in increasing knowledge of dental and oral health.